Mineral chemistry of the Tissint meteorite: Indications of two‐stage crystallization in a closed system. (5th October 2016) - Liu, Yang; Baziotis, Ioannis P.; Asimow, Paul D.; Bodnar, Robert J.; Taylor, Lawrence A.
Abstract: The Tissint meteorite is a geochemically depleted, olivine‐phyric shergottite. Olivine megacrysts contain 300–600 μm cores with uniform Mg# ( 80 ± 1) followed by concentric zones of Fe‐enrichment toward the rims. We applied a number of tests to distinguish the relationship of these megacrysts to the host rock. Major and trace element compositions of the Mg‐rich core in olivine are in equilibrium with the bulk rock, within uncertainty, and rare earth element abundances of melt inclusions in Mg‐rich olivines reported in the literature are similar to those of the bulk rock. Moreover, the P Kα intensity maps of two large olivine grains show no resorption between the uniform core and the rim. Taken together, these lines of evidence suggest the olivine megacrysts are phenocrysts. Among depleted olivine‐phyric shergottites, Tissint is the first one that acts mostly as a closed system with olivine megacrysts being the phenocrysts. The texture and mineral chemistry of Tissint indicate a crystallization sequence of: olivine (Mg# 80 ± 1) → olivine (Mg# 76) + chromite → olivine (Mg# 74) + Ti‐chromite → olivine (Mg# 74–63) + pyroxene (Mg# 76–65) + Cr‐ulvöspinel → olivine (Mg# 63–35) + pyroxene (Mg# 65–60) + plagioclase, followed by late‐stage ilmenite and phosphate. The crystallization of the Tissint meteorite likely occurred in two stages: uniform olivine cores likely crystallized under equilibrium conditions; and a fractional crystallization sequence that formed the rest of the rock. The two‐stage crystallization without crystal settling is simulated using MELTS and the Tissint bulk composition, and can broadly reproduce the crystallization sequence and mineral chemistry measured in the Tissint samples. The transition between equilibrium and fractional crystallization is associated with a dramatic increase in cooling rate and might have been driven by an acceleration in the ascent rate or by encounter with a steep thermal gradient in the Martian crust.